EVALUATION OF NEUROLOGICAL COMPLICATIONS USING WHO WARNING SIGNS FOR DENGUE DISEASE SEVERITY - Akmal, Ayesha; Tauseef, Ambreen; Akram, Tanzeela; Ali, Zaima; Zulfiqar, Sibgha; Umer, Naima (Pakistan Journal of Physiology, 2015)
In 2009 a new classification of dengue was proposed by WHO Tropical Disease Research, which classifies dengue into dengue (D), dengue with warning signs (DW) and severe dengue (SD). This classification highlights the warning signs of dengue disease severity. Neurological complications are one of the most serious complications of dengue disease. This study was carried out to see association of neurological complications of dengue patients with WHO warning signs for dengue disease severity, and their outcome. Methods: It was a cross-sectional analytical study and included 180 diagnosed and registered cases of dengue hemorrhagic fever. The participants were subjected to a detailed clinical evaluation, laboratory assessment including blood counts, hematocrit, serology for dengue fever and sonography at 24 hours and 48 hours of their admission. Results: Twenty-six percent patients were suffering from neurological complications due to dengue. The warning signs for dengue disease severity like altered sensorium (85.5%, pË‚0.001), raised hematocrit (n=47, p=0.029), gall bladder wall thickening, pleural effusion and ascites on sonographic report (n=47, p=0.024), were strongly associated with the neurological complications. Conclusion: Our study reveals significant association of WHO warning signs for dengue disease severity with neurological complications of dengue disease.